2020
DOI: 10.46549/jipvet.v10i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Bentonite Clay Dan Karbon Aktif Sebagai Aflatoksin Binders Berdasarkan Gambaran Imunologis Dan Histopatologis Pada Ayam Buras

Abstract: Aflatoxin is a toxic compound from the fungus A. flavus which can cause a decrease in chicken productivity. This study aims to evaluate the effect of bentonite clay and activated charcoal in chicken feed as aflatoxin binders based on histopathological and immunological features in chickens. A total of 60 chickens were randomly divided into 4 groups (G0, G1, G2, and G3) each group consisted of 15 chickens. G0 as a control without the addition of aflatoxin to the feed. Groups G1, G2, and G3’s feed were added wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…T. mycotoxinivorans is a yeast cell isolated from the hindgut of the termite Mastotermes darwiniensis and has been investigated as having the potential to degrade mycotoxins, including ochratoxin [ 9 ]. In addition, bentonite is an adsorbent that attaches to aflatoxins in the digestive tract so that the aflatoxins are not absorbed by digestion [ 11 ]. This is in accordance with a previous study by Hanif and Muhammad [ 23 ], which showed that T. mycotoxinivorans contained in detoxifying agents can reduce the adverse effects of ochratoxin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…T. mycotoxinivorans is a yeast cell isolated from the hindgut of the termite Mastotermes darwiniensis and has been investigated as having the potential to degrade mycotoxins, including ochratoxin [ 9 ]. In addition, bentonite is an adsorbent that attaches to aflatoxins in the digestive tract so that the aflatoxins are not absorbed by digestion [ 11 ]. This is in accordance with a previous study by Hanif and Muhammad [ 23 ], which showed that T. mycotoxinivorans contained in detoxifying agents can reduce the adverse effects of ochratoxin.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with a previous study by Hanif and Muhammad [ 23 ], which showed that T. mycotoxinivorans contained in detoxifying agents can reduce the adverse effects of ochratoxin. Bentonite is an adsorbent capable of attaching to aflatoxins in the digestive tract so that aflatoxins are not absorbed by digestion [ 11 ]. Bentonite, which is included in the toxin binder, can effectively bind mycotoxin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pada penelitian yang dilakukan Ramandani et al (2020) tentang pengujian aflatoksin dimana hal ini dapat memberikan efek yang negatif khususnya pada manusia apabila secara tidak sengaja sumber makanan ataupun obat-obatan yang diambil dari bahan alam dikontaminasi aflatoksin. Ramandani et al (2020) juga didalam penelitiannya menyebutkan bahwa sumber kaolin yang mengandung bentonite mampu menetralisir apabila terdapat kandungan aflatoksin.…”
Section: Pengujian Keamanan Bahan Bakuunclassified